2012
DOI: 10.1097/nen.0b013e3182479b41
|View full text |Cite
|
Sign up to set email alerts
|

Differential Detection and Distribution of Microglial and Hematogenous Macrophage Populations in the Injured Spinal Cord oflys-EGFP-kiTransgenic Mice

Abstract: The acute inflammatory response that follows spinal cord injury (SCI) contributes to secondary injury that results in the expansion of the lesion and further loss of neurologic function. A cascade of receptor-mediated signaling events after SCI leads to activation of innate immune responses including the migration of microglia and active recruitment of circulating leukocytes. Because conventional techniques do not always distinguish macrophages derived from CNS-resident microglia from blood-derived monocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 68 publications
5
40
0
1
Order By: Relevance
“…In order to differentiate between microglial and monocyte origin of macrophages associated with the fibrotic scar, we used chimeric mice to demonstrate that microglia was present mostly in the glial scar while the fibrotic scar was comprised almost solely of hMΦ. Our results are consistent with previous studies that demonstrated different spatial distribution between microglia and hMΦ (Evans et al, 2014; Fenrich et al, 2013; Mawhinney et al, 2012; Popovich and Hickey, 2001). However, our study is the first to demonstrate their distribution in distinct portions of the glial and fibrotic scar.…”
Section: Discussionsupporting
confidence: 94%
“…In order to differentiate between microglial and monocyte origin of macrophages associated with the fibrotic scar, we used chimeric mice to demonstrate that microglia was present mostly in the glial scar while the fibrotic scar was comprised almost solely of hMΦ. Our results are consistent with previous studies that demonstrated different spatial distribution between microglia and hMΦ (Evans et al, 2014; Fenrich et al, 2013; Mawhinney et al, 2012; Popovich and Hickey, 2001). However, our study is the first to demonstrate their distribution in distinct portions of the glial and fibrotic scar.…”
Section: Discussionsupporting
confidence: 94%
“…In active lesion formation, the transition from early active MS lesions to late/inactive MS lesions is thought to be mediated by macrophage activation and redistribution of CNS macrophages rather than accumulation of recruited hematogenous macrophages. 61,62 A redistribution of macrophages to CNS lesions was also reported in a mouse model of spinal cord injury, 63 where blood-derived monocytes and macrophages were present diffusely throughout the spinal cord at 1 and 3 days after injury but coalesced into a lesion 7 to 14 days after injury before resolution of the lesion. 63 These similarities between HIVE and SIVE, MS, and spinal cord suggest that recruitment of hematogenous macrophages and redistribution of local macrophages are involved in CNS lesion formation.…”
Section: Early Cns Macrophages and Sive Lesionsmentioning
confidence: 58%
“…Thus, this discrepancy could be accounted in part to the presence or absence of macrophages derived from CNS-residing microglia or from blood-derived monocytes invading the most damaged regions at the rostral and caudal spinal levels (Mawhinney et al, 2012). Previous work have shown that after SCI, pro-inflammatory cytokines are upregulated by microglia and macrophages in the first few days after injury.…”
Section: Discussionmentioning
confidence: 99%